“I Am Not a Corrupt Criminal and What I Did Is Not Corruption!”: The Dynamics of Perceptions, Denial, and Understanding of What Corruption Is - Zainal Abidin; Idhamsyah Eka Putra; Yuliana Hanami; Sari Angraeni (Changing Societies & Personalities)
While a general definition has been made on which acts are considered illegal corruption, people’s understandings of what constitutes corruption behaviors are varied. The present research aims to understand the perceptions, interpretations, denials, and rationalizations of corruption by convicted perpetrators in Indonesia. How corruption is perceived and understood by perpetrators, and how these perceptions may be utilized as a basis for denying corruption accusations should be explored to have more understanding of the dynamics of corruption from the perspective of perpetrators. The data were obtained through in-depth interviews with five corruption convicts. The results show that the reasons the participants deny the accusation of corruption are as follows: (a) they know what corruption is and they believe what they do is not corruption; (b) corruption cases are political, so it is improper to call it corruption; (c) they consider themselves victims of a bad system; and (d) they think that everyone does it. Such understanding, then, is used as a tool for denial and rationalization. The findings indicate how corruption is perceived and understood can influence someone to commit corrupt acts.